Identification of breast cancer molecular targets interacting with molecules present in the fruits of Antidesma bunius: In silico network pharmacology - based analysis - MA, Funing (2021)
The fruit of Antidesma bunius has both medicinal and edible properties. In previous studies, the fruit extract of A. bunius showed anti-proliferation activity on breast cancer cells, but its functional components and anti-tumor mechanism are still unclear. In this research, the main active components of A. bunius fruits (detected by UHPLC-MS/MS) and the corresponding targets were analyzed by network pharmacology method, and its interactions were verified by molecular docking to explore the possible tumor suppressor mechanisms. A total of 24 active chemical components were screened from fruits extract of A. bunius，and 44 targets genes were intersected with breast cancer, among them, AKT1, ESR1, EGFR, EP300, ERBB2 and AR were the top core targets．The GO enrichment of target genes mainly involved processes of cellular lipid metabolism, response to hormones, tube development, and KEGG pathway analysis centers in cancer pathways present in  breast, pancreatic and non-small cell lung cancer．The flavonoids in the fruits of A. bunius showed strong binding to the core targets by molecular docking analysis. These results strongly suggest that the flavonoids in the fruit of A. bunius can inhibit proliferation of breast cancer through multiple targets, mainly by ERK and PI3K-AKT pathways.